Heteronanostructural metal oxide-based gas microsensors - Lin Liu; Yingyi Wang; Yinhang Liu; Shuqi Wang; Tie Li; Simin Feng; Sujie Qin; Ting Zhang (Microsystems & Nanoengineering, 2022)
Abstract The development of high-performance, portable and miniaturized gas sensors has aroused increasing interest in the fields of environmental monitoring, security, medical diagnosis, and agriculture. Among different detection tools, metal oxide semiconductor (MOS)-based chemiresistive gas sensors are the most popular choice in commercial applications and have the advantages of high stability, low cost, and high sensitivity. One of the most important ways to further enhance the sensor performance is to construct MOS-based nanoscale heterojunctions (heteronanostructural MOSs) from MOS nanomaterials. However, the sensing mechanism of heteronanostructural MOS-based sensors is different from that of single MOS-based gas sensors in that it is fairly complex. The performance of the sensors is influenced by various parameters, including the physical and chemical properties of the sensing materials (e.g., grain size, density of defects, and oxygen vacancies of materials), working temperatures, and device structures. This review introduces several concepts in the design of high-performance gas sensors by analyzing the sensing mechanism of heteronanostructural MOS-based sensors. In addition, the influence of the geometric device structure determined by the interconnection between the sensing materials and the working electrodes is discussed. To systematically investigate the sensing behavior of the sensor, the general sensing mechanism of three typical types of geometric device structures based on different heteronanostructural materials are introduced and discussed in this review. This review will provide guidelines for readers studying the sensing mechanism of gas sensors and designing high-performance gas sensors in the future.